Characterization of Bacterial Population Associated with Deterioration of Stored Kinnow Fruits (Citrus nobilis x Citrus deliciosa) - Toijam, Rogeshwori; Bali, Gagan Preet Kour (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Fresh and spoiled Kinnow fruits were collected from local market in Kharar, Punjab, India to isolate and identify the microbial factors that causes deterioration of stored Kinnow (Citrus reticulata), as well as to study the impact of temperature to fruits at different storage conditions. Several microorganisms, including bacteria and fungus, may thrive in ideal condition present within the fruits. Using the pour plate method, the infected portion of the fruit was utilised to isolate the bacteria by serial dilution. Healthy colonies were selected and sub-cultured. Two types of bacteria have been isolated. Following morphological analysis and biochemical characterization, Staphylococcus spp. and Escherichia coli were determined to be the responsible organism.